Descriptive taxonomy : the foundation of biodiversity research - Watson, M. F.; Lyal, Christopher H. C.; Pendry, Colin (The systematics association special volume ;)
"Department of Life Sciences, Natural History Museum, London, UK. We are living in an age where biodiversity is being lost at an unprecedented rate, with the well-documented problems of habitat destruction being compounded by the largely unknown future effects of Climate Change. High quality, accurate and reliable biodiversity data are needed by biologists, conservationists and environmental modellers to understand and assess the ecosystems in which they work, to produce effective conservation strategies, and to feed computer-generated models which predict what environments and habitats we might face"--